Harvesting asymmetric steering via non-identical detectors - Shu-Min Wu; Rui-Di Wang; Xiao-Li Huang; Zejun Wang (European Physical Journal C: Particles and Fields)
Abstract We investigate asymmetric steering harvesting phenomenon involving two non-identical inertial detectors with different energy gaps, which interact locally with vacuum massless scalar fields. Our study assumes that the energy gap of detector B exceeds that of detector A. It is shown that $$A→ B$$ A → B steerability is bigger that $$B→ A$$ B → A steerability, implying that the observer with a small energy gap has more stronger steerability than the other one. We find that the energy gap difference can enlarge the harvesting-achievable range of $$A→ B$$ A → B steering, while it can also narrow the harvesting-achievable range of $$B→ A$$ B → A steering at the same time. In addition, the maximal steering asymmetry indicates the transformation between two-way steering and one-way steering in some cases, showing that $$B→ A$$ B → A steering suffers “sudden death” at the point of this parameter. These results suggest that asymmetric steering exhibits richer and more interesting properties than quantum entanglement harvested from vacuum quantum field.